THE INFLUENCE OF STEAM-BASED PROJECT-BASED LEARNING MODELS ON STUDENTS' LEARNING OUTCOMES IN CLASS IV ENERGY TRANSFORMATION MATERIAL AT MIN 6 BIREUEN - Putri Susiana (BRIGHT VISION Journal of Language and Education, 2023)
The importance of choosing a learning model. A good learning model can be used to make the teaching and learning process more effective, meaningful and enjoyable. So that students will get learning outcomes that can meet the minimum completeness criteria (KKM). But the fact is that teaching and learning in class is still not optimal in using learning models. Based on these problems need an update. One of the meaningful, effective, and fun learning alternatives that can be applied in developing student competencies is to use the STEAM-based project based learning model. The formulation of the problem in this study is "Does the STEAM-based project-based learning model affect student learning outcomes in class IV energy transformation material at MIN 6 Bireuen". The purpose of this study was to determine the effect of the STEAM-based project based learning model on student learning outcomes in class IV energy transformation material at MIN 6 Bireuen. This study uses a quantitative approach. This type of research is quasi experimental design. The population in this study were all MIN 6 Bireuen students while the samples were all 20 grade IV students. Data collection techniques used tests, while data analysis techniques used SPSS Statistics 25 by using normality tests and to test hypotheses using paired sample t-tests. The results showed that the significance value (2-tailed) on the test was 0.000 <0.05, where the average value of the learning test results was 85.5. The average value obtained by these students can fulfill the KKM. So it can be said that there is an influence of the STEAM-based project-based learning model on student learning outcomes in energy transformation material